Evaluation of Marine Agarose Biomaterials for Tissue Engineering Applications - Irastorza-Lorenzo, Ainhoa (Int J Mol Sci, 2021)
Five agarose types (D1LE, D2LE, LM, MS8 and D5) were evaluated in tissue engineering and compared for the first time using an array of analysis methods. Acellular and cellular constructs were generated from 0.3–3%, and their biomechanical properties, in vivo biocompatibility (as determined by LIVE/DEAD, WST-1 and DNA release, with n = 6 per sample) and in vivo biocompatibility (by hematological and biochemical analyses and histology, with n = 4 animals per agarose type) were analyzed. Results revealed that the biomechanical properties of each hydrogel were related to the agarose concentration (p < 0.001). Regarding the agarose type, the highest (p < 0.001) Young modulus, stress at fracture and break load were D1LE, D2LE and D5, whereas the strain at fracture was higher in D5 and MS8 at 3% (p < 0.05). All agaroses showed high biocompatibility on human skin cells, especially in indirect contact, with a correlation with agarose concentration (p = 0.0074 for LIVE/DEAD and p = 0.0014 for WST-1) and type, although cell function tended to decrease in direct contact with highly concentrated agaroses. All agaroses were safe in vivo, with no systemic effects as determined by hematological and biochemical analysis and histology of major organs. Locally, implants were partially encapsulated and a pro-regenerative response with abundant M2-type macrophages was found. In summary, we may state that all these agarose types can be safely used in tissue engineering and that the biomechanical properties and biocompatibility were strongly associated to the agarose concentration in the hydrogel and partially associated to the agarose type. These results open the door to the generation of specific agarose-based hydrogels for definite clinical applications such as the human skin, cornea or oral mucosa.